2018
DOI: 10.1080/15548627.2018.1474994
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral monocytes induce cancer cell autophagy to facilitate the progression of human hepatocellular carcinoma

Abstract: Macroautophagy/autophagy is an important catabolic process mediating cellular homeostasis and plays critical roles in cancer development. Whereas autophagy has been widely studied in various pathological models, little is known about the distribution, clinical significance and regulatory mechanism of this process in human hepatocellular carcinoma (HCC). In the present study, we found that tumor tissues exhibited significantly increased levels of autophagy compared with non-tumor tissues, and cancer cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…Subsequent IHC staining for LC3 (Fig. A), a marker for autophagy, revealed similar levels of LC3 between VETC + and VETC – HCCs (Figure B). Compared to VETC – patients, VETC + patients achieved significantly more OS benefit from sorafenib therapy in both low LC3 (VETC + vs. VETC – : HR = 0.498 vs. 1.005; P interaction < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Subsequent IHC staining for LC3 (Fig. A), a marker for autophagy, revealed similar levels of LC3 between VETC + and VETC – HCCs (Figure B). Compared to VETC – patients, VETC + patients achieved significantly more OS benefit from sorafenib therapy in both low LC3 (VETC + vs. VETC – : HR = 0.498 vs. 1.005; P interaction < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Immunoblotting was performed as previously described. 32 Protein was extracted using a protein extraction kit (Thermo Fisher, Cat#89900) according to the manufacturer's instructions. SDS-PAGE was used to separate an equal amount of cellular proteins.…”
Section: Immunoblottingmentioning
confidence: 99%
“…17,[24][25][26][27][28][29][30] For example, our previous studies showed that tumoractivated monocytes (Mos)/Mφs secrete cytokines, such as TNFα, IL-1β and IL-6, to enhance tumor cell autophagy and angiogenesis in HCC. 31,32 Given the critical role of Mos/Mφs in regulating tumor progression, we speculated that it would, in turn, influence the phagocytic signaling on tumor cells, thus resulting in impaired phagocytic clearance of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the invasion of peripheral areas by HCC tumors has been associated with higher levels of autophagy in HCC cancer cells [10]. Autophagy promotes HCC cell proliferation through the induction intracellular ATP via mitochondrial oxidative phosphorylation [11].…”
mentioning
confidence: 99%